PENERAPAN PENDIDIKAN KRISTIANI BERBASIS MULTIKULTURAL DI TORAJA SULAWASI SELATAN - Indayani Embong Bulan; Reinda Belolamba, Novita Maya Sari, Mitra Sambira, Narlis Tipak (ADISAM PUBLISHER, 2025)
Education is the main foundation in building quality human resources that are competitive and have character. This article discusses the importance of education as the main pillar in creating a golden generation that is ready to face global challenges. By highlighting the role of education in shaping moral values, critical skills, and innovation, this article explores how inclusive, adaptive, and technology-based approaches can strengthen education systems in the modern era. Apart from that, it also discussed the importance of collaboration between government, educational institutions and society in creating an educational ecosystem that supports lifelong learning. By focusing on teacher quality, relevant curriculum, and equitable access to education, this article invites all parties to play an active role in building the nation's future through empowering and meaningful education. The main hope is to create a generation that is not only intelligent, but also has integrity